The results of the study conducted in 2022 at the necropolis medieval settlement Syganak (Journal of history, 2022)
A mausoleum is a monument, a funeral building that included a chamber where the remains of the dead were placed. The Turkic peoples have built mausoleums over the graves of their dead ancestors for centuries. Mausoleums were considered the afterlife home of the dead. The erected structures make it possible to determine the social status of people buried in the mausoleum or to which class they belonged. After all, it is known that huge mausoleums were built for famous people, consisting of several rooms, with internal and external walls covered with decorative ceramics. The mausoleums had one or more burials. The graves studied and the materials found in them allow us to determine the status, outlook, way of life, traditions, religious beliefs and burial rites of the inhabitants. For this reason, in this article, we set the task of analyzing the studies conducted in 2022 at mausoleums No. 6 and No. 7 and introducing the data obtained during archaeological excavations into scientific circulation. Conducted scientific research within the framework of this topic made it possible to determine the features of mausoleums No. 6 and No. 7, construction technology and construction time. As a result of a comparative analysis with the mausoleums of this type from adjacent regions, the similarities and differences between the mausoleums of Syganak were determined. In addition, in the article we considered it appropriate to present the history of the emergence and development of mausoleums. In the article, when studying the little-studied history of the formation of mausoleums located in the middle reaches of the Syr Darya River, it is known that mausoleums arose on the basis of the ancient funeral tradition of nomadic peoples living in Central Asia.